PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEB PADA SMK ABDI SEJATI KERASAAN-I - Christiani Sinaga; Jamaluddin Jamaluddin; Eva Julia Gunawati Harianja; Roni Jhonson Simamora (Universitas Methodist Indonesia, 2022)
Admission of new students is one of the processes in educational institutions that is useful for screening prospective students who are selected according to the criteria determined by the school to become their students. Many schools use the internet for the development of new student admissions information systems. However, the information system for new student admissions at SMK Abdi Sejati Kerasaan-I is still manual. With the admission process that is still manual, it makes prospective students feel difficult and of course requires a faster and more efficient registration. The purpose of this research is the development of a manual system into a more efficient system. For this reason, a system is designed to speed up the web-based new student registration process that can be accessed via a web browser. This new student admissions information system was built using the PHP programming language and MySQL as the database. The results of this study are a web-based new admissions system that already has the ability to make it easier for prospective students to obtain information about new student admissions and the online registration payment validation process. Keywords: New student registration, web, PHP and MySQL